P53-MDM2 Pathway: Evidences for A New Targeted Therapeutic Approach in B-Acute Lymphoblastic Leukemia - Trino, Stefania; De Luca, Luciana; Laurenzana, Ilaria; Caivano, Antonella; Del Vecchio, Luigi; Martinelli, Giovanni; Musto, Pellegrino (Frontiers in Pharmacology, 2016)
The tumor suppressor p53 is a canonical regulator of different biological functions, like apoptosis, cell cycle arrest, DNA repair and genomic stability. This gene is frequently altered in human tumors generally by point mutations or deletions. Conversely, in acute lymphoblastic leukemia (ALL) genomic alterations of TP53 are rather uncommon, and prevalently occur in patients at relapse or with poor prognosis. On the other hand, p53 pathway is often compromised by the inactivation of its regulatory proteins, as MDM2 and ARF. MDM2 inhibitor molecules are able to antagonize p53-MDM2 interaction allowing p53 to exert tumor suppressor transcriptional regulation and to induce apoptotic pathways. Recent preclinical and clinical studies propose that MDM2 targeted therapy represents a promising anticancer strategy restoring p53 dependent mechanisms in ALL disease. Here, we discussed the use of new small molecule targeting p53 pathways as a promising drug target therapy in ALL.